A high-performance soybean meal-based plywood adhesive prepared via an ultrasonic process and using significantly lower amounts of chemical additives. (20th November 2020) - Yue, Li; Shi, Ruiqing; Yi, Zhang; Shi, Sheldon Q.; Gao, Qiang; Li, Jianzhang
Abstract: The development of a formaldehyde-free, high-performance soybean meal (SM)-based adhesive for manufacturing cleaner wood-based panels is important for minimizing environmental pollution and promoting sustainability. However, the addition of chemical agents for this purpose negatively impacts the environment. Drawing from molecular recombination enhancement theory, a simple physical ultrasonic treatment was used to pretreat the SM to break its particles down and reduce the protein molecular weight. A bio-derived crosslinker was mixed into the SM to recombine the soy protein and prepare a clean, high-performance, bio-based adhesive requiring significantly lower amounts of chemical agents. After 20 min of ultrasonic treatment, the SM particle size was reduced by up to 48.8%, the quaternary structure of the soybean protein was destroyed, and the protein molecular weight decreased, exposing more active groups on the protein surface and resulting in an adhesive system that was both more stable and had a higher reactivity. Moreover, when adding only 4% crosslinker and zero denaturing agent, the ultrasonic treatment process increased the adhesive residual rate by 15.78%, decreased the moisture absorption rate by 25.26%, and improved the wet shear strength of the resultant plywood by 368.2% (to 1.03 MPa), meeting the requirements of the GB/T 9846.3–2004 standard for interior-use plywood. The loading of chemical agents was reduced by up to 650% in comparison to that used in other SM-based adhesive formulations reported in the literature. Thus, using a clean ultrasonic pretreatment process on the SM enabled the preparation of a high-performance, stable, and clean SM-based adhesive, thereby providing a promising option for the implementation of a bio-based product in industrial applications. Graphical abstract: Image 1 Highlights: A cleaner and high-performance soybean meal-based adhesive was developed. Ultrasonic treatment breaks soybean protein molecule and exposes active groups. Using only 4% crosslinker recombines protein molecule to develop a denser structure. After 20 min UT, the wet shear strength of resultant plywood increased by 368%. UT reduces the dosage of chemical reagent for soybean meal adhesive by up to 650%.